Lembaga Petani Kelapa Sawit Sebagai Wadah Pengembangan dan Modernisasi Sawit Rakyat - Jongkers Tampubolon; albina ginting; Hotden Leonardo Nainggolan (Jurnal Visi Pengabdian Kepada Masyarakat, 2021)
Farmer institutions have a function as a forum for the learning process for farmers, a vehicle for cooperation, providers of production facilities and infrastructure, production units, processing and marketing units, and supporting service units. This service activity aims to; a) provide understanding for farmers about the benefits of farmer group institutions as a forum for obtaining capital or financing for smallholder oil palm rejuvenation sourced from the government; b) to provide understanding for farmers in forming smallholder oil palm farmer groups, as a condition for obtaining assistance from the Palm Oil Plantation Fund Management Agency (Badan Pengelola Dana Perkebunan Kelapa Sawit/BPDPKS). Based on service activities; a) an increase in the number of farmers who understand the existence of a government program on smallholder oil palm rejuvenation; b) there is an increase in the number of farmers who understand that the government provides financial assistance to farmers to rejuvenate and develop their oil palm farming; c) there is an increase in the number of farmers who understand that the government through BPDPKS can provide production facilities in the form of subsidized fertilizer for smallholder oil palm farmers; d) there is an increase in the number of farmers who understand that participation in cooperative institutions or farmer groups is a requirement to get government assistance in developing their oil palm farming.